ARTIFICIAL INTELLIGENCE (AI) AND AUTOMATION IN TAX LAW ENFORCEMENT - Loso Judijanto; Ratna Jaya (Adisam Publisher, 2025)
Artificial Intelligence (AI) and automation are changing the way tax law enforcement is conducted. These technologies offer advanced analytics capabilities that can identify tax fraud and law violations more effectively through complex data analysis. With automation, processes administrative can be streamlined, reducing human error and improving efficiency and speed in handling tax law cases. In addition, the application of these technologies has the potential to increase transparency and accountability in the tax system, provide more accurate and faster services to taxpayers and ensure fair application of regulations. Thus, AI and automation not only improve compliance and reduce operational costs, but also build public trust in the tax system.